2001
DOI: 10.1210/jcem.86.9.7861
|View full text |Cite
|
Sign up to set email alerts
|

TNFα Down-Regulates the Fas Ligand and Inhibits Germ Cell Apoptosis in the Human Testis

Abstract: The cytokine TNFalpha is known to be secreted by testicular germ cells. However, its effect on maturing germ cells is unknown, and its role in the regulation of spermatogenesis is unclear. Here we aimed at characterizing the effects of TNFalpha on germ cell survival in the human testis. We found that TNFalpha effectively and dose-dependently inhibited germ cell apoptosis, which was induced in vitro by incubating segments of human seminiferous tubules under serum-free culture conditions. EMSAs indicated increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…Moreover, numerous spliced variants of ERb have been detected in human testicular cells (Aschim et al 2004). Therefore for human seminiferous tubules there are controversial data (table 1) indicating either the absence (Pelletier & El-Alfy 2000) or the presence of ERa and ERb (Pentikaïnen et al 2000;Makinen et al 2001;Saunders et al 2001Saunders et al , 2002. It is of note that Cheng et al (1981) were the first to show a specific binding of oestradiol to human sperm; it was only in 1998 that Durkee et al demonstrated the presence of ERa in human spermatozoa, data that were later confirmed by Luconi et al (2006).…”
Section: Aromatase and Oestrogen Receptors In Human Testicular Cells mentioning
confidence: 99%
“…Moreover, numerous spliced variants of ERb have been detected in human testicular cells (Aschim et al 2004). Therefore for human seminiferous tubules there are controversial data (table 1) indicating either the absence (Pelletier & El-Alfy 2000) or the presence of ERa and ERb (Pentikaïnen et al 2000;Makinen et al 2001;Saunders et al 2001Saunders et al , 2002. It is of note that Cheng et al (1981) were the first to show a specific binding of oestradiol to human sperm; it was only in 1998 that Durkee et al demonstrated the presence of ERa in human spermatozoa, data that were later confirmed by Luconi et al (2006).…”
Section: Aromatase and Oestrogen Receptors In Human Testicular Cells mentioning
confidence: 99%
“…They concluded that the Fas system may have another role in male reproduction instead of, or in addition to, apoptosis. Pentikainen et al (50) demonstrated that the expression of the FasL was down-regulated by tumor necrosis factor alpha controlling physiologic germ cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm previous reports that described the initiation of apoptosis in testis during normal spermatogenesis (46,47), and support the hypothesis that spermatozoa with activated caspases detected in ejaculates (23,48) might have escaped an initial apoptotic process during spermatogenesis. Indeed, apoptosis has been shown to be a regulatory process that controls physiologic spermatogenesis (49,50). The efficient phagocytosis of apoptotic germ cells by Sertoli cells (43,51) in human testis with active and normal spermatogensis may explain the higher number of viable spermatozoa with staining of activated caspases (Caspþ/PIÀ) in the testicular than in the epididymal sample because these testicular spermatozoa would be phagocyted before reaching to the epididymis.…”
Section: Brugnon Caspases In Sperm Of Cbavd Patients Fertil Steril mentioning
confidence: 99%